2016
DOI: 10.1186/s12866-016-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Helicobacter pylori levofloxacin resistance and novel genetic mutation in Nepal

Abstract: BackgroundThe prevalence of Helicobacter pylori antibiotic susceptibility in the Nepalese strains is untracked. We determined the antibiotic susceptibility for H. pylori and analyzed the presence of genetic mutations associated with antibiotic resistance in Nepalese strains.ResultsThis study included 146 consecutive patients who underwent gastroduodenal endoscopy in Kathmandu, Nepal. Among 42 isolated H. pylori, there was no resistance to amoxicillin and tetracycline. In contrast, similar with typical South As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 48 publications
2
57
0
1
Order By: Relevance
“…40 Miftahussurur et al reported that mutations at Asn-87 and/or Asp-91 were predominantly in levofloxacinresistant strains, and the gyrB mutation had a steady relationship with gyrA 87-91 mutations. 41 None of the substitutions found in gyrB proved conferring resistance in this study. These findings revealed that the mutations of genes related to H. pylori resistance are diversified, especially in children.…”
Section: Discussionmentioning
confidence: 58%
“…40 Miftahussurur et al reported that mutations at Asn-87 and/or Asp-91 were predominantly in levofloxacinresistant strains, and the gyrB mutation had a steady relationship with gyrA 87-91 mutations. 41 None of the substitutions found in gyrB proved conferring resistance in this study. These findings revealed that the mutations of genes related to H. pylori resistance are diversified, especially in children.…”
Section: Discussionmentioning
confidence: 58%
“…Another observation was the detection of a D99N substitution (gyrA) in an isolate phenotypically levofloxacin resistant (MHP11). A previous study from Nepal found that a mutation at this position confers resistance, but a D99V substitution was noted (40). WGS revealed clinically significant mutations in isolates testing phenotypically sensitive, which highlights an advantage of WGS over phenotypic testing.…”
Section: Discussionmentioning
confidence: 76%
“…We examined our isolates for point mutations that may be associated with metronidazole resistance and found a mutation at position R16 that was associated with six of the eight phenotypically resistant isolates that lacked a truncation in rdxA ( Table 2; Table S2). This mutation has previously been associated with metronidazole phenotypic resistance (37,39,40). The detection of either a truncated rdxA gene or a mutation at position R16 correlated (kappa coefficient, 0.76) with 88% of phenotypic testing results (Table 2).…”
Section: Resultsmentioning
confidence: 85%
“…A significant and welcome increase was noted over the last year in the number of studies addressing the important topic of antimicrobial resistance in H. pylori infection. These are summarized in Table . A key message emerging is the relentless rise in antibiotic resistance, especially to clarithromycin and levofloxacin.…”
Section: Antimicrobial Resistancementioning
confidence: 99%